Real-Time Performance Evaluation for 5G Multi-Link Communication in Industrial Application - Da Liu; Yanling Zhao; Gongdai Liu; Congbo Wang; Lingyun Zhou; Ying Qian (IEEE Access)
The rapid advancement of network communication technologies has unlocked significant potential for advanced manufacturing industries. This new wave of industrial transformation, known as the Industry 4.0 era, is characterized by the integration of cutting-edge technologies such as Fifth Generation mobile communication technology (5G). Experimental commercial 5G deployments in factories have been reported, but these applications are generally limited to specific use cases. At present, there are no foundational standards for 5G in production lines, and its industrial adoption remains in the exploratory phase. This motivates an in-depth investigation into the potential of 5G for practical applications in production workshops, with a particular focus on evaluating its real-time performance in the presence of concurrent operations. This research focuses on the latency and packet loss performance of multi-link communication between multiple programmable logic controllers to evaluate the system’s real-time performance and reliability. By using different scenarios and parameter settings, and introducing other concurrently running services as background interference, it conducts extensive measurements and comprehensively analyzes the behavior of the resulting data. The empirical results indicate that the latency of the 5G system increases with higher load, particularly when concurrent services are running. However, adding more links does not lead to a significant increase in system latency, indicating the system’s robustness. Measured results also demonstrate the system’s high reliability in multi-link setups. The abnormal latency behavior can be caused by increased load and background interference, emphasizing the need for enhancing 5G performance to meet the high real-time requirements of industrial applications.